The effect of purslane seeds on glycemic status and lipid profiles of persons with type 2 diabetes: A randomized controlled cross-over clinical trial - Esmaillzadeh, Ahmad; Zakizadeh, Elahe; Faghihimani, Elham; Gohari, Mahmoodreza; Jazayeri, Shima (Journal of research in medical sciences, 2015)
Background: We are aware of limited data about the effects of purslane on diabetes. Earlier studies have mostly indicated the beneficial effects in animal models. This study aimed to evaluate the effect of purslane seeds on glycemic status and lipid profiles of persons with type 2 diabetes. Materials and Methods: This cross-over randomized controlled clinical trial was conducted on 48 persons with type 2 diabetes. Participants were randomly assigned to receive either 10 g/day purslane seeds with 240 cc low-fat yogurt (intervention group) or only 240 cc low-fat yogurt (as a control group) for 5 weeks. After a 2-week washout period, subjects were moved to the alternate arm for an additional 5 weeks. At baseline and end of each phase of the study, fasting blood samples were collected to quantify plasma glucose levels, as well as serum insulin and lipid profiles. Within-group and between-group changes in anthropometric measures, as well as biochemical indicators, were compared using a paired-samples t-test. Results: Mean age of study participants was 51.4 ± 6.0 year. We found a significant reduction in weight (−0.57 vs. 0.09 kg, P = 0.003) and body mass index (−0.23 vs. 0.02 kg/m 2 , P = 0.004) following purslane seeds consumption. Despite a slight reduction in fasting plasma glucose levels (−2.10 vs. −2.77 mg/dL, P = 0.90), we failed to find any significant effect on serum insulin levels and homeostatic model of assessment of insulin resistance score. Furthermore, purslane consumption decreased serum triglyceride levels (−25.5 vs. −1.8 mg/dL, P = 0.04) but could not affect serum high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and total cholesterol levels. We observed a significant reduction in systolic blood pressure (−3.33 vs. 0.5 mmHg, P = 0.01) and a borderline significant decrease in diastolic blood pressure (−3.12 vs. −0.93 mmHg, P = 0.09) after purslane seeds intake. Conclusion: In summary, consumption of purslane seeds for 5 weeks in persons with type 2 diabetes might improve their anthropometric measures, serum triglyceride levels, and blood pressure. Further studies are required to determine the appropriate dosage for these patients.